FOOD PRESERVATION TECHNIQUES: HOW TECHNOLOGY IS CHANGING THE WAY WE STORE AND CONSUME FOOD (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article explores the various food preservation techniques that have been used throughout history and how technology is revolutionizing the way we store and consume food. From ancient methods such as salting and drying to modern advancements like vacuum sealing and irradiation, the evolution of food preservation has greatly impacted our ability to extend the shelf life of perishable goods. This article delves into the advantages and disadvantages of different preservation methods, as well as the environmental and health implications of using technology in food storage.